THE FOREIGN EXCHANGE TRANSACTION EXPOSURE OF ENTERPRISES IN SERBIA - Bogićević, Jasmina; Dmitrović Šaponja, Ljiljana; Pantelić, Marija (Economic Annals, 2016)
Enterprises involved in international business face transaction exposure to foreign exchange risk. This type of exposure occurs when an enterprise trades, borrows, or lеnds in foreign currency. Transaction exposure has a direct effect on an enterprise’s financial position and profitability. It is one of the three forms of exposure to exchange rate fluctuations, the other two being translation exposure and operating exposure. The aim of this paper is to assess the transaction exposure of enterprises in Serbia operating internationally. In addition to identifying and measuring transaction exposure, this paper explores the practical importance that enterprises in Serbia attach to management of this type of foreign exchange risk. We do not find significant differences between domestic and foreign enterprises in their choice of the type of foreign exchange risk exposure to manage. Although transaction exposure is the most managed type of foreign exchange risk, research has shown that, compared to foreign businesses, Serbian enterprises do not use sufficient protective measures to minimize the negative impact of this type of exposure on their cash flows and profitability. We expected that there would be a statistically significant dependence between the volume of enterprises’ foreign currency transactions and the level of applied transactionexposure management practices. However, the results of our research, based on a sample of enterprises in Serbia operating internationally, show that transaction exposure management practices can be influenced by factors other than the level of an enterprise’s foreign currency transactions, such as the enterprise’s country of origin.